2015
DOI: 10.1007/s00449-015-1384-9
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Aspergillus ficuum phytase production in fed-batch and continuous fermentations in the presence of talcum microparticles

Abstract: This study aimed to enhance Aspergillus ficuum phytase production in fed-batch and continuous fermentations with addition of talcum microparticles. Phytase activity almost doubled in fed-batch and continuous fermentations by addition of 15 g/l of talcum compared to the control. Effect of talcum on fungal morphology was also shown that addition of talcum provided smaller fungal pellets and more homogenized fermentation broth compared to the control. Average fungal pellet radius decreased from 500 to 100 µm by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 18 publications
0
15
0
1
Order By: Relevance
“…For instance, fructofuranosidase and glucoamylase activities were increased to 150 U/mL (3.7-fold) and 190 U/mL (9.5-fold) with the addition of 25 g/L of titanate compared to control, respectively (Driouch et al 2012). Moreover, Coban et al (2015a) performed the production of fungal phytase in microparticle-enhanced fed-batch bioreactor. The highest phytase activities were found as 9.6 U/mL with the addition of 15 g/L of talcum while it was 4.9 U/mL without microparticle.…”
Section: Mannanase Production In Fed-batch Biofilm Reactormentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, fructofuranosidase and glucoamylase activities were increased to 150 U/mL (3.7-fold) and 190 U/mL (9.5-fold) with the addition of 25 g/L of titanate compared to control, respectively (Driouch et al 2012). Moreover, Coban et al (2015a) performed the production of fungal phytase in microparticle-enhanced fed-batch bioreactor. The highest phytase activities were found as 9.6 U/mL with the addition of 15 g/L of talcum while it was 4.9 U/mL without microparticle.…”
Section: Mannanase Production In Fed-batch Biofilm Reactormentioning
confidence: 99%
“…Moreover, the batch processes have some disadvantages such as limitation of operating time, re-inoculation requirement for each fermentation, time loss due to cleaning and sterilization for each fermentation, substrate or product inhibition as well as low resistance against share force. All those things cause low fermentation efficiency, weakness of cell viability or stability, high recovery cost, low production yield and productivity (Bai et al 2008;Coban et al 2015a;Germec et al 2015). To overcome such problems, different fermentation methods such as immobilization (El-Naggar et al 2006), biofilm formation using support materials (Ercan and Demirci 2015a;Germec et al 2015), and the usage of microparticles such as aluminum oxide (Al 2 O 3 ), magnesium silicate (Talcum, 3MgOÁ4SiO 2 ÁH 2 O), and titanium silicate oxide (Titanate, TiSiO 4 ) have been studied (Coban et al 2015a;Yatmaz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Gonciarz and Bizukojc ( 2014 ) and Gonciarz et al ( 2016 ) studied lovastatin-producing Aspergillus terreus ATCC 20542 and cultivated it in shake flasks with talc microparticles (Gonciarz and Bizukojc 2014 ), and in batch and continuous fed-batch stirred-tank bioreactors (Gonciarz et al 2016 ). Similarly, Coban et al ( 2015a , b ), who studied the enhancement of phytase production by Aspergillus ficuum NRRL 3135 with addition of talc or aluminum oxide, started with shake flasks and then continued in fed-batch and continuous bioreactors. This team later changed their interests to lactic acid production by Rhizopus oryzae NRRL 395 (Coban and Demirci 2016 ).…”
Section: Microparticle-enhanced Cultivation Of Filamentous Fungimentioning
confidence: 99%
“…Coban et al ( 2015a , b ) reported that the addition of microparticles to the A. ficcum NRRL 3135 culture decreased average fungal pellet size and prevented bulk fungal growth. In shake flask cultivations the average fungal pellet radius decreased from 800 µm for control to 500 and 200 µm by increasing the particle concentration to 15 g l −1 of aluminum oxide and talc, respectively.…”
Section: Microparticle-enhanced Cultivation Of Filamentous Fungimentioning
confidence: 99%
See 1 more Smart Citation